Alanine rich peptide from Populus trichocarpa inhibit growth of Staphylococcus aureus via targetting its extracellular domain of Sensor Histidine Kinase YycGex protein. (August 2018) - Al Akeel, Raid; Mateen, Ayesha; Syed, Rabbani; Alqahtani, Mohammed S.; Alqahtani, Ali S.
Abstract: Background: Due to growing concern towards microbial resistance, ongoing search for developing novel bioactive compounds such as peptides is on rise. The aim of this study was to evaluate antimicrobial effect of Populus trichocarpa extract, chemically identify the active peptide fraction and finds its target in Staphylococcus aureus. Methods: In this study the active fraction of P. trichocarpa crude extract was purified and characterized using MS/MS. This peptide PT13 antimicrobial activity was confirmed by in-vitro agar based disk diffusion and in-vivo infection model of G. mellonella . The proteomic expression analysis of S. aureus under influence of PT13 was studied using LTQ-Orbitrap-MS in-solution digestion and identity of target protein was acquired with their quantified expression using label-free approach of Progenesis QI software. Docking study was performed with peptide PT13 and its target YycG protein using CABS-dock. Results: The active fraction PT13 sequence was identified as KVPVAAAAAAAAAVVASSMVVAAAK, with 25 amino acid including 13 alanine having M/Z 2194.2469. PT13 was uniformly inhibited growth S. aureus SA91 and MIC was determined 16 μg/mL for SA91 S. aureus strain. Sensor histidine kinase (YycG) was most significant target found differentially expressed under influence of PT13. G. mellonella larvae were killed rapidly due to S aureus infection, whereas death in protected group was insignificant in compare to control. The docking models showed ten docking models with RMSD value 1.89 for cluster 1 and RMSD value 3.95 for cluster 2 which is predicted to be high quality model. Conclusion: Alanine rich peptide could be useful in constructing as antimicrobial peptide for targeting extracellular Domain of Sensor Histidine Kinase YycG from S. aureus used in the study. Highlights: Many pathogens known to be virulent especially bacteria, viruses, and one of the known cause is microbial resistance. Its worthy to pinhole this concern area to be a key part in dwelling the root cause of the resistance. As there is an increasing rate of multidrug resistance staphylococcus aureus, present study could be useful in development new antimicrobial peptide drug. Which may combat the multidrug resistance S. aureus by targeting histidine kinase protein.